Recent Trends in Chronic Pelvic Pain Diagnosis - Ari Kim; Heung Yeol Kim (Kosin Medical Journal, 2012)
Chronic pelvic pain is a common and significant disorder of women. It is estimated to have a prevalence of 3.8% in women. The etiology of chronic pelvic pain in women is poorly understood. Although a specific diagnosis is not found in the majority of cases, some common diagnoses include endometriosis, adhesions, irritable bowel syndrome, and interstitial cystitis. The initial history and physical examination can narrow the diagnostic possibilities, guide any subsequent evaluation, and rule out malignancy or significant systemic disease. If the initial evaluation does not reveal a specific diagnosis, a limited laboratory and ultrasound evaluation can clarify the diagnosis, as well as rule out serious disease and reassure the patient. Laboratory and imaging studies should be selectively utilized, as should laparoscopy. Conscious laparoscopic pain mapping has been proposed as a way to improve information derived from laparoscopic evaluations.